POLITIQUE MONETAIRE, STABILITE DES PRIX ET DEVELOPPEMENT DE L’ACTIVITE ECONOMIQUE114 EN ZONE CEMAC - ArsѐneMba Fokwa; Ibrahim, Nji Ngouhouo; François, Kamajou (European Scientific Journal, ESJ, 2014)
The purpose of this paper is to examine the effects of the conflict between the objectives of price stability and that of employment in the CEMAC zone that caught the fight against inflation as its major economic objective. Writers such as Phillips (1958), Lucas (1972), Okun (1970), Nupukpo (2002) worked on the relationship between monetary policy and its purpose and economic activity. The data come from the World Bank, in World Development Indicators contained, in CD-ROM (WDI-2013), BEAC (Activity Reports BEAC). Working for the periods 1977-1994, 1995-2012 and 1977-2012. The analysis was done with a dynamic panel that has the distinction of being among the independent variables, the endogenous variable lagged one or more periods. The three endogenous variables are the inflation rate, the growth rate and the employment rate. The estimation method used is that of Arellano and Bond (1991); it has the advantage of correcting the bias that comes from the correlation between the lagged endogenous variable and the error term. The results show that the effects of monetary policy on economic activity (growth and employment) are mixed because the exchange rate is transmitted to inflation, monetary policy has no effect on inflation but in the economic activity. Inflation has its main source in trade with the outside and does not stimulate the economy. This economic activity is slowed by the sources of inflation, growth and employment have a negative effect on each other. While the causes of inflation are no longer those of external trade, the economy will be better in the CEMAC zone. For best contribution of monetary policy to economic activity, it is good to avoid the high variability of the interest rate that creates an unexpected or difficult and volatile inflation.